برصغیر کی مذہبی ، علمی اور ثقافتی تاریخ کی تحقیق میں شیخ محمد اکرام کا اسلوب اور خصائصMethodology and Characteristics of Sheikh Muhammad Ikrām’s research regarding Religious, Intellectual and Cultural History of the Subcontinent (Al-Qamar, 2021)
Among the studies that have come to light on the religious, cultural and intellectual history of the subcontinent, the three books (Āb-i-Kawsar, Rūd-i-Kawsar and Mawj-i-Kawsar) by Sheikh Muhammad Ikrām (1908-1973), a renowned Pakistani historian and biographer, are unique in nature. This paper presents a study of Ikrām’s methodology and characteristics of his writing in the referred works. From the two parts of this study, the first deals with the biographical outline and scholarly position of Sheikh Mohammad Ikrām and the second part explains the methodology and features of his works. The study finds that Ikrām’s style in his referred works is academic, critical and literary, as well as lively, comprehensive and fascinating. While studying his writings, the reader walks with him throughout the history. He analyzes historical situations and personalities as a critic and then draws conclusions in such a way that the reader becomes imperceptibly convinced of his arguments.
Keywords: History; Subcontinent; research; Ikrām